2020
DOI: 10.1007/s40123-020-00232-2
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Fixation of the Fluocinolone Acetonide Implant in Eyes with Severe Iris–Lens Diaphragm Disruption and Recalcitrant CME: The Fluocinolone-Loop-Anchoring Technique (FLAT)

Abstract: Introduction: While proven to be an effective treatment for cystoid macular edema (CME) and diabetic macular edema, intravitreal steroid implants (IVSI) may cause undesirable side effects, including steroid-related glaucoma or migration into the anterior chamber in the case of iris-lens diaphragm disruption. Here we present a new surgical technique that allows for the easy implantation and subsequent fixation of the fluocinolone acetonide intravitreal implant without the risk of migration as a feasible and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…e eligibility was accessed in 19 studies, and a total of 11 were included in this review. Of these 11 studies, 6 are case reports [20][21][22][23][24][25], 1 is a case series [26], 1 is an abstract [27], 1 is a retrospective study [28], and 2 are randomized control trials [29,30]. e main characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…e eligibility was accessed in 19 studies, and a total of 11 were included in this review. Of these 11 studies, 6 are case reports [20][21][22][23][24][25], 1 is a case series [26], 1 is an abstract [27], 1 is a retrospective study [28], and 2 are randomized control trials [29,30]. e main characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Herold et al [ 25 ] reported two patients with disrupted anterior-posterior segment border and persistent CME. Both patients (1 eye each) were treated with a DEX implant, and both patients experienced problems related to the implant or migration of the implant into the anterior chamber.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical procedure of scleral fixation of the fluocinolone acetonide implant (Iluvien, Alimera Sciences Inc, Alpharetta, GA) was performed under local anesthesia with retrobulbar injection of lidocaine or sub-tenon anesthesia according to the protocol of the FLAT-technique that has been described before. 10 …”
Section: Methodsmentioning
confidence: 99%